Including a symposium on 50 years of the Union for Radical Political Economics - Fiorito, Luca, 1967-; Scheall, Scott; Suprinyak, Carlos Eduardo (Research in the history of economic thought and methodology, 2019)
Volume 37A of Research in the History of Economic Thought and Methodology features a symposium edited by Tiago Mata, celebrating 50 years of the Union of Radical Political Economics. It also includes an essay by Mauro Boianovsky, and is accompanied by a series of reflections from esteemed colleagues, all focused on Arthur Lewis and the classical foundation of development economics. The Volume further includes an important new archival contribution (edited and introduced by Malcolm Rutherford) from the papers of Alvin Hansen, in which the famous Harvard economist reflects on the contributions of his teacher, John R. Commons, on the occasion of the latter's 70th birthday in November 1932.